2018
DOI: 10.2139/ssrn.3141340
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Contribution of the BSUP (JNNURM) to Inclusive Cities in India

Abstract: The Basic Services for the Urban Poor (BSUP) sub-Mission of the Jawaharlal Nehru National Urban Renewal Mission (JNNURM) sought to address the needs of some of the lowest-income and most vulnerable urban dwellers in Indian cities. The promise was that these residents would receive 'a garland of 7 entitlements' -security of tenure, affordable housing, water, sanitation, health, education and social security in low-income settlements in the 63 Mission cities. We researched the outcomes of the BSUP in five Indian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…An assessment of the Indian government’s Basic Services for the Urban Poor (BSUP) programme”, Environment and Urbanization Vol 25, No 1, pages 177–188. For recent work on housing policy in India specifically, see Burra, S, D Mitlin and G Menon with I Agarwal, P Banarse, S Gimonkar, M Lobo, S Patel, V Rao and M Waghmare (2018), “Understanding the contribution of the BSUP (JNNURM) to inclusive cities in India”, Effective States and Inclusive Development (ESID) Working Paper No 97, University of Manchester, Manchester, available at http://www.effective-states.org/working-paper-97/. See also Bhan, G (2018), “Housing, common sense and urban policy in India”, in H Bhurte and A Bhide (editors), Urban Parallax Policy and the City in Contemporary India , Yoda Press, New Delhi.…”
mentioning
confidence: 99%
“…An assessment of the Indian government’s Basic Services for the Urban Poor (BSUP) programme”, Environment and Urbanization Vol 25, No 1, pages 177–188. For recent work on housing policy in India specifically, see Burra, S, D Mitlin and G Menon with I Agarwal, P Banarse, S Gimonkar, M Lobo, S Patel, V Rao and M Waghmare (2018), “Understanding the contribution of the BSUP (JNNURM) to inclusive cities in India”, Effective States and Inclusive Development (ESID) Working Paper No 97, University of Manchester, Manchester, available at http://www.effective-states.org/working-paper-97/. See also Bhan, G (2018), “Housing, common sense and urban policy in India”, in H Bhurte and A Bhide (editors), Urban Parallax Policy and the City in Contemporary India , Yoda Press, New Delhi.…”
mentioning
confidence: 99%
“…An initial draft of the paper was shared with city-based and UK researchers and refined, following their inputs. The discussion has also been informed by my involvement in two earlier studies of shelter outcomes and government urban poverty programming in urban India and Uganda, supported by the DFID-funded research centre on Effective States and Inclusive Development (Burra et al 2018;King and Kasaija 2018). The research has had a city focus, with limited interviewing of national government officials and politicians.…”
Section: : Methodologymentioning
confidence: 99%
“…Watson (2014) finds the 'strength, reliability and form of civil society', state devolution, and the transnational demonstration of alternatives to be critical. Similarly, in India, Burra et al (2018) find that levels of devolution, levels of local income and wealth, and civil society capacity have been key to increasing the extent to which co-produced housing developments have generated satisfactory solutions for the urban poor. Banana et al (2015) find that ensuring quality, accessibility and affordability requires resources to be identified that can subsidise services and secure the replication of effective models of delivery at scale.…”
Section: Co-production and Urban Poverty Reductionmentioning
confidence: 99%
“…Our conceptual framing has been guided by research into settlement transformation in India, which examined the dynamics of state vision, commitment and capacity within the Basic Services for the Urban Poor sub-mission of the Jawaharlal Nehru National Urban Renewal Mission (Burra et al, 2018). Conceptually, we were concerned to understand under what conditions more progressive ideas about inclusive urban development and poverty reduction emerge, what shapes state commitment to delivering inclusive development and urban poverty reduction, and what capacities enable states to contribute to such outcomes, including a particular interest in the role of civil society within these dynamics.…”
Section: Conceptual Frameworkmentioning
confidence: 99%